1985
DOI: 10.1159/000260825
|View full text |Cite
|
Sign up to set email alerts
|

A Scanning Electron Microscopic Study of Surface Changes during Development of Artificial Caries

Abstract: Crowns of human molars were exposed to lactate buffers, pH 5.0, with or without diphosphonate (MHDP) for periods of 1 h to 10 days. The changes in the enamel surface appearance were observed by scanning electron microscope (SEM) at up to × 40,000, and lesion progress was assessed by chemical analysis and polarized light microscopy. In both model systems subsurface caries-like demineralization was produced. The SEM observations showed that the opening up of the intercrystalline spaces by acid over the entire ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 11 publications
2
24
0
Order By: Relevance
“…It is also possible that enamel abrasion played a role in the reduction of fluorescence loss. It has been reported that abrasion or polishing of demineralized surfaces can result in the exposure of more tightly packed crystals [Holmen et al, 1985] explaining the change in ⌬ F. However, this cannot be the only mechanism responsible as the fluoride-containing groups clearly exhibited statistically superior remineralization.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that enamel abrasion played a role in the reduction of fluorescence loss. It has been reported that abrasion or polishing of demineralized surfaces can result in the exposure of more tightly packed crystals [Holmen et al, 1985] explaining the change in ⌬ F. However, this cannot be the only mechanism responsible as the fluoride-containing groups clearly exhibited statistically superior remineralization.…”
Section: Discussionmentioning
confidence: 99%
“…The SEM photographs show qualitatively an increase in the number of features, which will increase the surface roughness. Holmen et al [1985] suggested from SEM studies of the development of artificial caries that acid exposure opened up the intercrystalline spaces, thus it is to be expected that there would be an increase in surface roughness.…”
Section: Main Experimentsmentioning
confidence: 99%
“…12 Based on chemical analysis and histopathological observations, the initial stage of caries development is characterized by the opening of the intercrystalline spaces without the destruction of the surface and subsequent creation of microchannels. [13][14][15] These microchannels are found to be about 0.5 to 1.5 μm in width in artificial lesions 5 and range from 0.2 to 1.0 μm in width in early natural enamel lesions. 16 When white spot lesions (the early stage of demineralized enamel) are hydrated/wet, microchannels in lesions are filled with fluid/water.…”
Section: Introductionmentioning
confidence: 99%